PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP MOTIVASI KERJA PEGAWAI NAKES PUSAT MATA NASIONAL RUMAH SAKIT MATA CICENDO - Any Wahyu Mumpuni (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2023)
The purpose of this study was to determine the effect of education and training (training) on ​​the work motivation of National Eye Center Employees at Cicendo Eye Hospital. This study used a quantitative descriptive method, and used questionnaires, interviews, and documentation as data collection techniques. The measuring instrument or tool used is a training questionnaire which also serves as an interview guide, and a work motivation scale. The population of this study were health workers at Cicendo Eye Hospital with a sample of 36 (thirty six) people. From the results of processing, observation and interviews, it was found that there is a strong and significant relationship between education and training (training) and employee motivation. One of the factors related to individual employee performance and productivity is work motivation, so it is very important to continuously increase employee motivation through increased education and training activities.